Is lowering blood pressure hazardous in patients with significant ipsilateral carotid stenosis and acute ischaemic stroke? Interim assessment in the 'Efficacy of Nitric Oxide in Stroke' Trial - Sare, G.M. (2016)
10.1097/MBP.0b013e32831e30bd